Analisis Penerapan E-Government Dalam Peningkatan Kualitas Pelayanan Administrasi Kependudukan Pada Mal Pelayanan Publik Bojonegoro - Dhani Amatulloh (Dialogue : Jurnal Ilmu Administrasi Publik, 2021)
This study focuses on the application of e-government in the quality of public administration services at the Bojonegoro Public Service Mall. The establishment of this Public Service Mall is an effort to create one stop services. The aim of the Government of Bojonegoro Regency takes the initiative to create a Public Service Mall is to make the community easier to manage various types of services. The purpose of this study was to investigate the implementation of e-government on the quality of public administration services and the inhibiting and supporting factors of the implementation of e-government, and to formulate strategies to increase the success of e-government implementation carried out by the Department of Population and Civil Registration at the Bojonegoro Public Service Mall. This study employed a descriptive approach. Data collection techniques were carried out by observation, interviews, and documentation. The data analysis were carried out by data collection (data collection), data reduction (data reduction), data display (data display), verification and confirmation of conclusions (Conclusion drawing and verification). The results of the study, according to formulated by R. Eko Indrajit (in Azkiya, 2018: 4), elucidate the following: 1, Efficiency: The public administration service process through the Si N'duk application, there has been no convenience, speed, and time efficiency because the application was not working optimally. 2. Effectiveness: there were system constraints that make the program less effective. 3. Transparency: Socialization of Si N'duk application and the availability of information both about work programs and other matters regarding to public services existed. 4. Accountability: there was a clarity of employee accountability mechanism in inputting data from Si N'duk application. 5. Empowerment: there was socialization from the office to the sub-district. Supporting factors of Si N'duk application were the support from the Regency Government in encouraging online media to disseminate information related to Si N'duk application and the support from internal employees. Meanwhile, the inhibiting factors were the lack of budget, network or system disturbances, and many people have no understanding and knowledge about Si N'duk application. Keywords: E-Government, Public Service Mall, Public Administration.